Performa Udang Hias Red Cherry (Neocaridina heteropoda) pada Fase Pembesaran Melalui Aplikasi Warna Wadah Berbeda - Subamia, I Wayan; Himawan, Yogi (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2014)
Shrimp red cherry shrimp is one of the ornamental potential developed. One of the conservation efforts can be made to increase production by optimizing keragaannya on enlargement phase. This study aims at scaling up the production of red cherry shrimp, especially in the phase of enlargement. Treatment in the form of background color is composed of (A) without colors (control), (B) white, (C) in black, and (D) red. Each treatment was repeated three times with a 45-day long research. Container maintenance in the form of an aquarium measuring 14x14x14 cm3 volume of 1 l and equipped with aeration. The prawns used were 10 fish / aquarium with a weighted average of 0.018 ± 0.21 g and the total length of the average of 0.82 ± 0.21 cm. Feeding in the form of an ad bloodworm satiation and include aquatic plant Hydrilla sp. as a source of additional food and shelter in the form of detritus. The results showed that the weight gain and the highest long background color was achieved by treatment D (red) which is equal to 0.09 ± 0.3 g and 1.62 ± 0.3 cm. Survival at each treatment reached 100%. The water quality of all treatments during the study period remained within normal limits.